SPATIAL-ORGANIZATION OF FORAGING ACTIVITY AND COLONIZATION BY COLONY EMIGRATION IN THE PHARAOH ANT, MONOMORIUM-PHARAONIS - Fowler, H. G. (Gustav Fischer Verlag Jena, 1993)
Using food bait stations and colony trap nests, the spatial relation between the foraging activity of established colonies of the polygynous and unicolonial exotic pharaoh's ant, Monomorium pharaonis, and colonization by colony fragments was studied over an 8 month period in a large institutional setting in Brazil. Both foraging activity and colonizations demonstrated significant spatial clumping. However, colonizations were significantly negatively clumped spatially with respect to foraging activity. This suggests that the colonization strategy of this species under the studied conditions was that of complete habitat domination.
Keywords: COLONIZATION; FORAGING; SPATIAL ANALYSIS; MONOMORIUM-PHARAONIS; BRAZIL; SPATIAL CORRELOGRAMS